Immunotherapy for Recurrent and Metastatic Cervical Cancer: A Review - Yuke Wu; Xiang He (IMR Press, 2024)
Objectives: This review aims to summarize the current literature on recurrent and metastatic (r/m) cervical cancer, especially first-line and second-line immunotherapy. Clinical benefits including efficacy and safety of new therapeutic options are also reviewed. Mechanism: The published relevant articles were searched from multiple databases, including PubMed, Ovid, and Scopus. The key terms included recurrent cervical cancer, advanced cervical cancer, metastatic cervical cancer, and immunotherapy. The data of the latest clinical trials was retrieved from ClinicalTrials.gov (https://clinicaltrials.gov). Findings in Brief: In late 2021, pembrolizumab in combination with chemotherapy with or without bevacizumab was approved as the first-line treatment for recurrent and metastatic cervical cancer. Also tisotumab vedotin was approved as the second-line immunotherapy for r/m cervical cancer. Moreover, a plethora of clinical immunotherapy trials were approved in different countries, and some received as breakthrough therapy designations. Pembrolizumab, cemiplimab, atezolizumab, cadonilimab, zimberelimab, balstilimab and zalifrelimab, nivolumab, and tisotumab vedotin were reviewed with overall survival, progression-free survival, rate of objective response and adverse effects in order to review the efficacy and safety of different therapeutic option. Conclusions: The majority of trials indicated that immunotherapy can significantly improve the overall survival (OS) and progression-free survival (PFS) of r/m cervical cancer patients without negatively affecting health-related quality-of-life (HRQoL), and demonstrated that immunotherapy is an effective and safe treatment for r/m cervical cancer.